The making of 'loyals' and 'rebels': the 1880 Transkei Rebellion and the Subversion of the chieftaincies of East Griqualand, 1874-1914 - Snell, Milner Charles (Rhodes University, Faculty of Humanities, Department of History, 2017)
In the mid-1870s, influenced by the mineral revolution in southern Africa, the Cape responsible government began to extend colonial rule over the chiefdoms that inhabited the Mthatha- Mzimkhulu region. Although white officials initially negotiated with the leadership of these chiefdoms to accept colonial rule and depended heavily on them to implement new laws, ultimately the Cape government aimed to side-line indigenous political systems and replace them with magistrates and headmen. Colonial officials mistakenly equated indigenous political structures with dictatorial chiefs whose followers were subject to their personal ambitions. In fact chiefs were part of a collective leadership and were very aware and influenced by the needs of their adherents. This work is concerned with how the chieftaincies, or indigenous political systems, of the Mthatha-Mzimkhulu region responded, survived and adapted in the face of colonialism. The chieftaincies were remarkably resilient despite the political and economic changes brought on by colonialism and capitalism and were able to retain some degree of authority amongst their followers and at times obtain recognition from the colonial state. Interactions between the chieftaincies and the colonial state were complex, fluid and ever evolving. Some leaders of chiefdoms co-operated with colonial authorities, either over particular issues at certain times or more generally over longer periods, and were considered by colonial officials to be 'loyal'. Yet, at other times they resisted the demands and changes being brought on by colonialism and were labelled as 'rebels'. Questions of how the chieftaincies responded to colonial rule were most critical during the Transkei Rebellion of 1880, which is a central focus of this work. Some chieftaincies co-operated with and served with the colonial military forces in order to spare themselves from the economic and social disruption brought on by war and the confiscation of land by the victors. Other chieftaincies took up arms against the colonial state in an attempt to stop the increasingly unacceptable demands being made of them and to resist the negative changes that colonialism was bringing. Despite their ability to adapt, by the early years of the twentieth century hereditary leaders found themselves increasingly caught between the expectations of their followers and demands made by the colonial administration. Faced with increasing popular criticism, many leaders adapted ambiguous and shifting stances on issues concerning their followers.
Keywords: Uncatalogued